Diretrizes para desenvolvimento de projeto para ligações de painéis de fachada horizontais de concreto pré-moldado - Uehara, Fábio Nori (2009)
The increasing of using precast concrete panels, lack of standardization, lack of studies on precast concrete panels and its connections devices on Brazil, has led to the need of manual and design criteria of precast concrete panel connections. Although the designers and precast concrete panel manufacturers is using foreign standards when its available and their empirical knowledge on the specification and connections design criteria, the lack of manuals become hard to find solutions that provide easiness of precast concrete panel s employment. Connections are fundamental part of the precast structures. For the building assembly are necessary linking devices which influences the production process, the efficiency of casting, storage, transport, handling and especially in the assembly on site. This work presents the concept, technical features and functions of main types of spandrel panel connections and the main structure of building, and identifies typical connections and the general design recommendation. This report purpose the put in connection as a new classification of connection type.